Coherent structures detected in the unstable atmospheric surface layer above the Amazon forest - Dias Júnior, Cléo Quaresma (Journal of Wind Engineering and Industrial Aerodynamics, 2020)
Some characteristics of the turbulence structure above primary forest localized in the south-western Amazon are analyzed. The data was collected in 60. m height meteorological tower erected in Rebio-Jarú Reserve, Brazil. The Morlet's wavelet is used to detect coherent structures (CS) "ramp" time scales from turbulent virtual temperature data measured above forest, under day-time conditions. It is shown that there is a close relationship between time scale of the coherent structure (TCS) and the height to the inflection point in the mean wind speed profile (IP). A time scale associated with the IP is used to provide useful information on inside canopy penetration flow in order to be compared with the CS time-scale. The results show a very robust correlation between these two time scales (for 144 half-hourly data sets, a correlation coefficient value of 0.9 have been obtained). Such results provide new insights regarding shear instability and turbulent eddy characteristics above tall vegetation, in the surface roughness sub-layer (SRS). © 2013 Elsevier Ltd.